Кримінальна делінквентність як об’єкт гуманітарних наук - Слинько, С. В.; Slynko, S. V.; Слинько, Д. С.; Slynko, D. S.; Филин, Д. В.; Fylyn, D. V.; Стратонов, В. М.; Stratonov, V. M. (Наше право. - 2020. - № 4. - С. 47-54, 2020)
Обґрунтовано існування нової теоретичної конструкції – кримінальної делінквентністі, яка об’єднує юридичні феномени злочину, кримінального правопорушення та кримінального проступку. Розкрито теоретичні підходи дослідження кримінальної делінквентністі. Запропоновано визначення єдиної термінології та обґрунтовано положення, що включають до себе не тільки особу правопорушника, а викриває соціальні, правові умови вчинення кримінального злочину, правопорушення, проступку.

Amendments to the current legislation of Ukraine have established new provisions that should combine the construction of general and special theory of criminal law and process into a single terminological definition, provide elements of gender disposition that should reveal not only legal content, but also provide practical significance for criminal justice. General theories of criminal law and process have significant contradictions in the definition of legal terminology, which in substantive law are defined as a crime, given the structure of this type. The rules of criminal procedure indicate a criminal offense, but do not provide a theoretical justification for this category. Administrative law introduces the concept of offense and introduces it into criminal law and procedure. A pre-trial investigation in the form of an inquiry into criminal offenses must be conducted by an investigator. Science has set new tasks for determining criminal offenses and criminal offenses. Based on the general provisions of criminal, administrative law and process, the existence of a new theoretical construction is substantiated - criminal delinquency, which combines non-legal phenomena of crime, criminal offense and criminal offense. Theoretical approaches to the study of criminal delinquency are revealed. A proposal is made to define a single terminology and the provisions of this category are substantiated, which includes not only the identity of the offender, but also exposes the social conditions of committing a criminal offense, offense, misdemeanor.

Обосновано существование новой теоретической конструкции – криминальной делинквентности, объединяющей юридические феномены преступления, уголовного правонарушения и уголовного проступка. Раскрыты теоретические подходы исследования криминальной делинквентности. Предложено определение единой терминологии и обоснованы положения, включающие в себя не только личность правонарушителя, а изобличающие социальные, правовые условия совершения уголовного преступления, правонарушения, проступка.
Слинько, С. В. Кримінальна делінквентність як об’єкт гуманітарних наук / Слинько Сергій Вікторович, Слинько Дмитро Сергійович, Филин Дмитро Вітальович, Стратонов Василь Миколайович // Наше право. - 2020. - № 4. - С. 47-54. - DOI: 10.32782/NP.2020.4.8.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; гуманітарні науки; humanities; гуманитарные науки; делінквентність; delinquency; делинквентность; кримінальна делінквентність; criminal delinquency; криминальная делинквентность; кримінальне правопорушення; criminal offence; уголовное правонарушение; кримінальний проступок; criminal misdemeanor; уголовный проступок; злочин; crime; преступление; органи кримінальної юстиції; bodies criminal justice; органы уголовной юстиции